Engineers' handbook of industrial microwave heating - Meredith, R. J. (Roger J.) (Institution of Engineering and Technology, 1998)
Heating materials using microwave energy offers many advantages in industrial processes, including improved quality, efficiency and control. There is a growing interest in microwave heating throughout industry and there are now many research establishments, both academic and industrial, working in this field. Microwave technology is a well developed science in the areas of radar and communications, supported by a large bibliography, but this is not the case for its applications to industry. The aim of this book is first to present the fundamentals of microwave technology that are relevant to industrial practice in a manner accessible to engineers, scientists and technicians who may have little or no prior knowledge of the subject. Second, it presents a perspective on the range and scope of the techniques and hardware used, giving detailed descriptions, making critical comparisons and commenting frequently on practical issues of design.